Cystathionine β-synthase affects organization of cytoskeleton and modulates carcinogenesis in colorectal carcinoma cells - Liskova, Veronika; Chovancova, Barbora; Babula, Petr; Rezuchova, Ingeborg; Pavlov, Kristina Ploth; Matuskova, Miroslava; Krizanova, Olga (Frontiers in Oncology, 2023)
Cystathionine-β-synthase (CBS), one of three enzymes that endogenously produce hydrogen sulfide, is extensively studied for its relevance also in various tumor´s cell. In our previous work we observed that immunofluorescence pattern of CBS is very similar to that from tubulin and actin. Therefore, we focused on potential interaction of CBS with cytoskeletal proteins β-actin and β-tubulin and functional relevance of the potential interaction of these proteins in colorectal carcinoma cell lines. To study potential interaction of CBS with cytoskeletal proteins and its functional consequences, CBS-knockout DLD1 (DLDx) cell line was established by using the CRISPR/Cas9 gene editing method. Interaction of selected cytoskeletal protein with CBS was studied by immunoprecipitation and Western blot analysis, immunofluorescence and proximity ligation assay. Functional consequences were studied by proliferation and migration assays and by generation of xenografts in SCID/bg mice. We have found that CBS, an enzyme that endogenously produces H2S, binds to cytoskeletal β-tubulin and to lesser extent also to β-actin in colorectal carcinoma derived cells. When CBS was knockouted by CRISPR/Cas9 technique (DLDx), we observed de-arranged cytoskeleton compared to unmodified DLD1 cell line. Treatment of these cells with a slow sulfide donor GYY4137 resulted in normal organization of cytoskeleton, thus pointing to the role of CBS in microtubule dynamics. To evaluate the physiological importance of this observation, both DLD1 and DLDx cells were injected into SCID/bg mice and size/mass of developed xenografts was evaluated. Significantly larger tumors developed from DLDx compared to DLD1 cells, which correlated with increased proliferation of these cells. Taken together, in colorectal cancer DLD1 cells, CBS binds to cytoskeleton, modulates microtubule dynamics and thus affects the proliferation and migration in colorectal carcinoma stable cell line.